2018
DOI: 10.1007/s00198-018-4444-6
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic screening for bone disease using abdominal CT scans obtained for other reasons in newly diagnosed IBD patients

Abstract: Using CT scans obtained for other indications, we found low rates of osteopenia and osteoporosis that may otherwise have gone undiagnosed. Refinement of opportunistic screening may have advantages in terms of cost-savings and earlier detection of bone loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
1
3
0
2
Order By: Relevance
“…In a Chinese population-based study, it was revealed that in men younger than 50 years, the prevalence of osteoporosis was 0.4% when femoral neck was measured and 2.1% when accessed with lumbar spine [ 22 ]. In the present study, the prevalence of osteoporosis in patients newly diagnosed with IBD is similar with that of the same age group in Chinese general population, which was also consistent with previous studies [ 15 , 16 ]. It has been reported that low BMD was more common in patients newly diagnosed with CD rather than UC [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a Chinese population-based study, it was revealed that in men younger than 50 years, the prevalence of osteoporosis was 0.4% when femoral neck was measured and 2.1% when accessed with lumbar spine [ 22 ]. In the present study, the prevalence of osteoporosis in patients newly diagnosed with IBD is similar with that of the same age group in Chinese general population, which was also consistent with previous studies [ 15 , 16 ]. It has been reported that low BMD was more common in patients newly diagnosed with CD rather than UC [ 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Of note, with prolonged course of the disease, bone loss aggravated in patients newly diagnosed with IBD [ 15 , 16 ]. The underlying risk factors contributing to the worsening of bone loss are complex and have not yet been fully revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Opportunistic screening for osteoporosis becomes increasingly popular [14, 45]. In contrast to numerous studies of opportunistic screening, where HU values in thoracic or lumbar vertebra were reported [33–35, 4650], we used asynchronous calibration to obtain lumbar trabecular BMD. Synchronous calibration with an in-scan phantom as in conventional QCT can be replaced by asynchronous calibration as in the opportunistic setting, if scanner stability is maintained [23].…”
Section: Discussionmentioning
confidence: 99%
“…Das führt zu zusätzlichen für die interne Kalibrierung charakteristischen Richtigkeitsfehlern [36]. Als Alternative zur internen Kalibrierung wurde vorgeschlagen, unkalibrierte HounsfieldEinheiten direkt zur Abschätzung des Frakturrisikos zu benutzen [37][38][39][40]. HU Werte sind aber CT Scanner spezifisch und abhängig von der Röhrenspannung, d. h. die Berechnung des Frakturrisikos ist Scanner und kV abhängig, eine Standardisierung scheint fast unmöglich.…”
Section: Opportunistic Screeningunclassified